Effect of melatonin and n-acetylcysteine on hepatic injury in rat induced by methanol intoxication: a comparative study - Koksal, M.; Kurcer, Z.; Erdogan, D.; Iraz, M.; Tas, M.; Eren, M. A.; Aydogan, T.; Ulas, T. (My University, 2012)
Background: Methanol intoxication leads liver injury; in contrast melatonin and n-acetyl cysteine (NAC) are known to have protective effects on liver.